Caracterização genética, fitoquímica e das atividades biológicas de diferentes populações naturais de Varronia Curassavica Jacq. e Momordica Charantia L. no Espírito Santo - Mota, Mainã Mantovanelli da (2019)
The medicinal plants have been used for treatment, cure and prevention of diseases for several thousands of years. Varronia curassavica and Momordica charantia are widely exploited plant species for therapeutic purposes. Varronia curassavica Jacq. popularly known as “erva-baleeira”, belongs to the family Cordiaceae and is traditionally used to treat inflammation, in addition it is described by present antibacterial, antifungal, anti-allergic, antitumor, and antioxidant properties. Already the Momordica charantia L. is a species herbaceous belonging to the family Cucurbitaceae commonly known as bitter gourd or bitter melon and in tradicional medicine, it is used for the treatment of diabetes, colics, cancer, among other disorders. The medicinal properties shown by different medicinal plants are due to the secondary metabolites present in the plant. However, genetics and environmental factors, such as soil composition, temperature, rainfall and ultraviolet radiation incidence can affect the concentrations of these chemical components that reflect on their biological activities. Therefore, the aim of this study was to evaluated the environmental and genetic factors influence on the production of secondary metabolites and the antioxidant, cytotoxic and antiproliferative activity of populations from different regions of Espírito Santo/Brazil of V. curassavica and M. charantia. The results obtained from the analyzes using ISSR molecular markers showed that both V. curassavica and M. charantia species showed a significant similarity between the analyzed populations, probably due to the fact these species possess variety of pollinators insect and seed dispersal animals which facilitated the gene flow. The phytochemical analyzes of V. curassavica revealed a significant quantitative difference between the samples tested, which reflected in variability in their biological antioxidant and antitumoral activities. Results strongly suggest that these variations were caused by environmental rather than genetic factors. The analyzes with the species M. charantia showed there is not a very large variation among the populations related as to their chemical content and biological activity, suggesting that for this plant the geographic location is not determinant for the quantitative and qualitative variation of phenolic compounds. The extract of both species showed a higher selective cytotoxicity in vitro against sarcoma 180, demonstrating that V. curassavica and M. charantia presents therapeutic potential for the development of new drugs. This work are important to help in elucidation optimal conditions for ethnopharmacological use of these medicinal plants.